The associations of self-reported salt-intake and spot urine sodium with home blood pressure - Wistrand, Henrik (My University, 2022)
A limited number of studies have suggested a nonlinear association between spot urine (SU) sodium concentration and office blood pressure (BP). We examined how SU sodium concentration and dietary salt obtained from a food frequency questionnaire associate with more accurately measured home BP in a large, nationwide population sample. We included 1453 participants in cross-sectional and 880 participants in 11-year longitudinal analyses. We investigated associations between baseline salt/sodium variables and (i) baseline and follow-up home BP; and (ii) prevalent and incident hypertension with linear and logistic regression models. We observed positive associations (β±standard error) between salt/sodium variables and BP in unadjusted models. SU sodium concentration associated with baseline systolic (0.04±0.01, P<0.001) and diastolic (0.02±0.01, P<0.001) BP and follow-up systolic (0.03±0.01, P=0.005) and diastolic (0.02±0.01, P<0.001) BP. Dietary salt intake was associated with baseline (0.58±0.20, P=0.003) and follow-up (0.73±0.23, P=0.001) systolic BP. Unadjusted odds of prevalent hypertension were higher in the highest quintile as compared to the lowest quintile of SU sodium concentration (odds ratio 1.66, 95% confidence interval 1.20-2.31). SU or dietary salt intake were not associated with incident hypertension. After adjustments for sex, age, body mass index and alcohol intake, none of the aforementioned associations remained statistically significant. We found no evidence of a J-shaped association between the salt/sodium variables and BP or hypertension. In conclusion, SU sodium concentration and dietary salt intake associated with home BP and hypertension only in some of the unadjusted models. Our results underscore that feasible estimation of sodium intake remains challenging in epidemiology.

Eräät tutkimukset ovat ehdottaneet kertavirtsanäytteen natriumpitoisuuden ja vastaanottoverenpaineiden välisen yhteyden olevan epälineaarinen. Tämän tutkimuksen tarkoituksena oli tutkia kahden eri suolamuuttujan, kertavirtsanäytteen natriumpitoisuuden ja ravintofrekvenssikyselyllä mitatun suolansaannin, ja verenpainetasoa tarkemmin kuvaavan kotiverenpaineen yhteyttä suuressa väestöaineistossa. Sisällytimme 1453 osallistujaa poikittaisiin ja 880 osallistujaa pitkittäisiin analyyseihin (11 vuoden seuranta-aika). Suolamuuttujien yhteyttä tarkasteltiin (i) lähtötilanteen ja seurantatilanteen kotiverenpaineisiin ja (ii) verenpainetaudin vallitsevuuteen ja ilmaantuvuuteen nähden lineaarisilla ja logistisilla regressiomalleilla. Positiivinen yhteys (β±keskihajonta) havaittiin vakioimattomissa malleissa suolamuuttujien ja verenpainearvojen välillä. Kertavirtsan natriumpitoisuus oli yhteydessä lähtötilanteen systoliseen (0.04±0.01, P<0.001) ja diastoliseen (0.02±0.01, P<0.001) verenpaineeseen, sekä seurantatilanteen systoliseen (0.03±0.01, P=0.005) ja diastoliseen (0.02±0.01, P<0.001) verenpaineeseen. Ravintokyselyllä mitattu suolansaanti oli yhteydessä systoliseen verenpaineeseen lähtötilanteessa (0.58±0.20, P=0.003) ja seurantatilanteessa (0.73±0.23, P=0.001). Vakioimattomissa malleissa vallitsevan verenpainetaudin todennäköisyys oli korkeampi korkeimmassa kertavirtsan natriumpitoisuuden kvantiilissa verrattuna alimpaan kvantiiliin (vetosuhde 1.66, 95% luottamusväli 1.20-2.31). Suolamuuttujat eivät olleet yhteydessä verenpainetaudin korkeampaan ilmaantuvuuteen. Kun edellä mainitut tilastolliset mallit vakioitiin lähtötilanteen iällä, sukupuolella, painoindeksillä ja alkoholinkäytöllä, yhteydet eivät säilyneet tilastollisesti merkitsevinä. J-käyrän mallisesta yhteydestä suolamuuttujien ja verenpaineen välillä ei löytynyt viitteitä. Tulokset alleviivaavat, että käytännöllinen suolansaannin arviointi on edelleen haastavaa epidemiologiassa.
Keywords: Avainsanat: verenpaine, verenpainetauti, suolansaanti, kertavirtsanäytteen natriumpitoisuus Keywords: blood pressure, hypertension, salt intake, spot urine sodium concentration